Clostridium Difficile Associated Diarrhea in Children with Hematological Malignancy-Experience from a Pediatric Oncologic Centre, Bangladesh - Begum, Ferdousi; Islam, Afiqul; Haque, Rashidul; Miah, Mohammad Abdal; Alam, Kazi Khairul; Karim, Mohammad Anwarul; Begum, Momena; Yasmin, Farida (International Journal of Child Health and Nutrition, 2019)
Background: Clostridium difficile Associated Diarrhea (CDAD) is considered to be one of the commonest causes of nosocomial diarrhoea worldwide. Gastrointestinal infections in the form of diarrhoea are common in pediatric oncology patients in Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh. The study was conducted to find out the frequency of Clostridium difficile infection (CDI) among diarrheal children with haematological malignancy. Materials and Methods: This prospective observational study was conducted from April 2012 to March 2013 at the Pediatric Hematology and Oncology Unit, BSMMU, Bangladesh. Total 58 diarrheal episodes occurred in 51 children with various types of haematological malignancies were included consecutively. Faecal samples of the children were sent to International Centre for Diarrheal Disease Research, Bangladesh (ICDDR, B) laboratory for detection of Clostridium difficile antigen (GDH) and toxins (A and/ or B) by Enzyme Immunoassay (EIA). Results: Among 58 diarrheal episodes 22.4% faecal samples were positive for GDH, but none of the faecal samples was positive for toxin A and or B. There were a significant association with leucopenia, severe neutropenia; usage of meropenem plus vancomycin, cefepime plus amikacin, imipenem, cytarabine and omeprazole with GDH positive diarrheal episodes. Conclusion: Positive GDH antigen with a negative result for toxin indicates C. difficile colonization. Among GDH positive episodes, a significantly higher proportion of children had leucopenia, severe neutropenia and usage of some drugs known as risk factors for C. difficile infection. To confirm the CDI advanced tests are needed.